Análisis de la publicidad de las Pymes de calzado de la provincia de Tungurahua - Sánchez Rosero, Cynthia Odalis (2023)
The objective of the thesis "Analysis of the advertising of footwear SMEs in the province of Tungurahua" was to develop a guide for the implementation of visual merchandising strategies in commercial spaces for footwear, based on effective advertising strategies. The footwear market in Tungurahua presents challenges for SMEs in effective promotion and advertising, facing shortcomings in attractive visual elements and applied technologies, and advertising without a strategic approach. The study aimed to identify shortcomings in the distribution of spaces, analyze visual elements in advertising, evaluate the use of applied technologies, and learn about customer preferences in order to develop a guide for visual merchandising strategies. A mixed approach was used, combining quantitative and qualitative methods. Surveys and interviews with owners and customers of footwear SMEs and bibliographic research were conducted to obtain relevant information. The proposed guide focuses on improving the layout of spaces, incorporating attractive visual elements and applied technologies, and considering customer preferences. The study showed that the implementation of visual merchandising strategies based on advertising strategies can improve the competitiveness and attractiveness of footwear SMEs